A photophysical and spectroelectrochemical study on N-phenyl-carbazoles and their oxidized species - Ramirez, Cristina Lujan (2018)
A series of N-phenyl-carbazole derivatives namely TCz (N-tolyl-carbazol), TCz-TCz (a 3,3´-linked dimer), and CzPh-CH2-PhCz (a methylene-bridged N-phenyl-carbazole), have been synthesized and studied by means of absorption and fluorescence spectra, DFT calculations, cyclic voltammetry and spectroelectrochemistry. It is concluded that the methylene bridge in CzPh-CH2-PhCz isolates the two TCz units, whereas TCz-TCz allows extending the electronic coupling along both carbazoles. Moreover, the phosphorescence spectrum of TCz-TCz showed a high energy triplet state (2.76 eV). It was observed that oxidation of CzPh-CH2-PhCz generates an electrochromic polymer containing TCz-TCz dimer units separated by methylene bridges. Oxidized TCz-TCz subunit was analyzed by EPR spectroscopy, and found to be a Class III mixed valence ion in Robin and Day classification. All results suggest that these molecules might be suitable as selective probes in fluorescence sensing or as host materials in electroluminescent devices.